Lesbenstich : eine Zeitung des Lesbenbewegung. (Düsseldorf : Lesbenstich Presse Verlag, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Birkenstrasse 19, D-4000 Düsseldorf 1
Duits
Periodiek